The Effect Of Using Webtoon On Students Writing Skill For The Seventh Grade Students - Rizma Indah Susanti; Erlik Widiyani; Vita Vendityaningtyas (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
The purpose of this study is to ascertain the impact of webtoons on students' narrative writing abilities in texts taught in first grade at SMPN 8 Madiun using the webtoon application. The words